Glemselens rom og erindringens sted: Skalering av industriell kulturarv i Odda og Tyssedal - Forrás, Peter (Tidsskrift for kulturforskning, 2025)
During the last decades a more holistic approach to heritage has made its way into cultural heritage management in the Nordic countries. Attention has shifted from the architectural or historical value of single buildings, and monuments, to a broader understanding of the heritage values of landscapes, historic urban environments and large-scale technical systems. The idea of cultural environment (“kulturmiljø”) has partly substituted and partly supplemented existing object-centered approaches to cultural heritage. Among other things, this entails an understanding of heritage through concepts drawn from the field of geography, such as setting, site or locality – and in particular the idea of place seems to be essential for upscaling heritage. However, this “spatial turn” – or rather “placial turn” – in cultural heritage management seems indifferent to how place unlike space plays into scaling in very different ways, and in general pays a minimum of attention to how heritagization is dependent upon spatial practices and scaling. Drawing on a case study of the heritagization of the twin industrial towns Odda and Tyssedal in western Norway, this paper examines how space, place and scaling are implicated in the construction of cultural memory of large-scale industrial heritage. The paper outlines how place became a core concept underpinning the turn from objects to cultural environments, and based on the spatial scale of industrial heritage in Odda and Tyssedal discusses how space can be brought back into the discourse on heritage.